Spatiotemporal dynamics of volatile flavor compounds and associated functional microbial communities during strong-flavor Daqu fermentation - Wenyi Jiang; Zhihua Li; Yi Dong; Zonghua Ao; Junjie Jia; Zhilin Chen; Chuan Song; Lei Yang; Ruidi Liu; Jie Peng; Suyi Zhang; Zhiping Feng (Food Microbiology, 2027)

The effect of nonlinear interactions between UFKW and Q16DW on the ionosphere - Ruidi Sun; Sheng-Yang Gu; Liuguan Ding; Yusong Qin; Min Jiang; Xiaodan Liu; Qiang Wang (Advances in Space Research, 2026)

Microplastic-affected pathogens in drinking water supply systems: Survival mechanisms, ecological impacts and control challenges - Ruidi Xu; Qiqi Wan; Ruihua Cao; Yanghui Xu; Huan Tang; Gang Liu; Gang Wen (Water Research, 2026)

Unraveling the effects of added Chuzhou chrysanthemum polysaccharides on the structure and physicochemical properties of instant kudzu starch: An interactive perspective - Ruidi He; Chengjin Liu; Xinyi Wang; Pengli Hu; Liping Yang (Food Research International, 2026)

In-Situ trace polymer intercalation endowing vanadium pentoxides with unique structural regulation for robust electrochromism - Yin Yan; Chenchen Bian; Ruidi Wang; Zhongqiu Yan; Meng Li; Pengyang Lei; Shiyou Liu; Ying Lv; Pan Li; Xin He; Kar Wei Ng; Ying Lv; et al. (Chemical Engineering Journal, 2026)

Insight into the roles of various additives on gasification reactivity of petroleum coke - Ruidi Wei; Liwei Ren; Shumin Wang; Lei Liu (Fuel, 2025)

Assessment of the gridded burden of disease caused by PM2.5-bound heavy metals in Beijing based on machine learning algorithm and DALYs - Tong Lyu; Xin Meng; Yilin Tang; Yidan Zhang; Yue Gao; Wei Zhang; Xu Zhou; Ruidi Zhang; Yue Sun; Siqi Liu; Tianqing Guo; Jianan Zhou; et al. (Science of The Total Environment, 2025)

Integrating knowledge-data-driven method to predict load-displacement curve on a trapdoor - Hui Zeng; Xing-Tao Lin; Deng Wang; Xiangsheng Chen; Dong Su; Ruidi Chen; Wei Liu (Computers and Geotechnics, 2025)

The Role of MicroRNA-206 in the Regulation of Diabetic Wound Healing via Hypoxia-Inducible Factor 1-Alpha - Zeming Bai; Dapeng Zhou; Kai Tao; Feng Lin; Hongyi Wang; Haiwei Sun; Ruidi Liu; Zhe Li (Biochemical Genetics, 2025)
Successful wound healing in diabetic patients is hindered by dysregulated miRNA expression. This study aimed to investigate the abnormal expression of miRNAs in diabetic wound healing and the potential therapeutic role of modulating the miR-206/HIF-1α pathway. MicroRNA assays were used to identify differentially expressed miRNAs in diabetic wound sites and adjacent areas. In vitro models and a rat diabetic model were established to evaluate the effects of miR-206 on HIF-1α regulation and wound healing. The study revealed differential expression of miR-206 in diabetic wound tissues, its interaction with HIF-1α, and the inhibitory effect of miR-206 on cell growth under high glucose conditions. Modulating the miR-206/HIF-1α pathway using miR-206 antagomir promoted HIF-1α, CD34, and VEGF expression, ultimately enhancing diabetic wound healing.

Backwater rise upstream of a stream-crossing culvert due to large wood accumulation and sediment deposition - Qiang Li; Ruihua Nie; Lu Wang; Ruidi Bai; Xingnian Liu; Chao Liu (Journal of Hydrology, 2025)

Recommendations for the reference concentration of cadmium exposure based on a physiologically based toxicokinetic model integrated with a human respiratory tract model - Yilin Tang; Tong Lyu; Hongbin Cao; Wei Zhang; Ruidi Zhang; Siqi Liu; Tianqing Guo; Xu Zhou; Yanxue Jiang (Journal of Hazardous Materials, 2024)

Vertical 3D printing of rGO/CNTs arrays for thermal interface materials with in-situ local temperature monitoring function - Ruidi Xia; Shuaikang Zhu; Fangzheng Zhen; Yu Du; Jianwei Zhang; He Yang; Miao Wu; Bo Zhao; Zhenyi Qi; Minsu Liu; Lin Jiang; Zhiqiang Liang (Chemical Engineering Journal, 2024)

Experimental investigation of bubbly flow and air entrainment discharge downstream of chute aerators - Ruidi Bai; Shanjun Liu; Zhong Tian; Wei Wang; Faxing Zhang (Environmental Fluid Mechanics, 2019)